Formulation and Characterization of Bilastine – Ternary Cyclodextrin Inclusion Complex - Al-Khedairy, Eman B. H.; Salam Hatam, Sura (Iraqi Journal of Pharmaceutical Sciences, 2025)
Abstract Bilastine (BLA) is a modern second – generation antihistamine employed to manage symptoms associated with allergic rhinoconjuctivitis and urticaria. However, it is very slightly soluble in water with low bioavailability, which affects its therapeutic action. The main objective of this research was to enhance the solubility and dissolution rate of BLA by complexation technique using beta cyclodextrin)β-CD) and its derivatives, hydroxypropyl beta cyclodextrin) HP-β-CD), methyl beta cyclodextrin(M-β-CD), and sulfobutyl ether beta cyclodextrin (SBE-β- CD) . Binary and ternary complexes using different hydrophilic polymers were prepared using kneading, solvent evaporation, co-grinding, and microwave methods. The resulting complexes were characterized for their percentage yield, drug content, solubility, and dissolution. The best complex was further characterized by XRD and FT-IR. The obtained results revealed that the ternary complex consisting of BLA, M-β CD, and soluplus ® (1mole /1mole / 5% w/w ) prepared by solvent evaporation method, exhibited the highest solubility (7.8 times more than the pure BLA) and the fastest release rate, where 90 % of BLA was released within the first 15 minutes at pH 6.8 with percentage yield of 89.3 % and 100 % drug content. Furthermore, the FTIR analysis confirmed the inclusion of BLA within the cavity of M-β CD. Additionally, the XRD diffractograms indicated the amorphous nature of the resulting complex